2020
DOI: 10.1021/acs.jpclett.0c02616
|View full text |Cite
|
Sign up to set email alerts
|

Charge Redistribution Mechanisms in SnSe2 Surfaces Exposed to Oxidative and Humid Environments and Their Related Influence on Chemical Sensing

Abstract: Tin diselenide (SnSe2) is a van der Waals semiconductor, which spontaneously forms a subnanometric SnO2 skin once exposed to air. Here, by means of surface-science spectroscopies and density functional theory, we have investigated the charge redistribution at the SnO2–SnSe2 heterojunction in both oxidative and humid environments. Explicitly, we find that the work function of the pristine SnSe2 surface increases by 0.23 and 0.40 eV upon exposure to O2 and air, respectively, with a charge transfer reaching 0.56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…The Se contribution cannot be attributed to SeO 2 , as this contribution is centered at much higher binding energy, around 59.5 eV. 75,78 Alternatively, the formation of SnSe 2Àx metastable phase can be considered. Indeed, D'Olimpio et al 75 did a careful investigation of SnSe 2 chemistry when exposed to different environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Se contribution cannot be attributed to SeO 2 , as this contribution is centered at much higher binding energy, around 59.5 eV. 75,78 Alternatively, the formation of SnSe 2Àx metastable phase can be considered. Indeed, D'Olimpio et al 75 did a careful investigation of SnSe 2 chemistry when exposed to different environment.…”
Section: Resultsmentioning
confidence: 99%
“…75,78 Alternatively, the formation of SnSe 2Àx metastable phase can be considered. Indeed, D'Olimpio et al 75 did a careful investigation of SnSe 2 chemistry when exposed to different environment. However, this would imply also a contribution on the Sn signal, and this contribution would be between SnSe 2 and SnSe, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 Spontaneous oxidation of chalcogenides represents, indeed, an excellent opportunity to synthesize new kinds of interfaces comprising thin layers of amorphous metal oxides grown over 2D layered crystalline materials, yielding a-MO/TMD and a-MO/MC heterostructures with unexpected applications in the field of catalysis and gas sensing. 25 On this account, we recently demonstrated by means of experiments and theory that it is possible to synthesize a-SnO 2 /SnSe 2 heterostructures to detect NO 2 , H 2 , NH 3 , and humidity 26,27 by controlled oxidation in air of 2D exfoliated SnSe 2 layers. Besides their excellent gas sensing response, these 2D amorphous/2D crystalline heterostructures unfortunately retain some remarkable limitations.…”
mentioning
confidence: 99%
“…55,56 Roy et al 57 have reported 4.6 eV as the work function of SnSe 2 . D'Olimpio et al 58 reported that this discrepancy in the work function values is due to the surface oxidation of SnSe 2 at room temperature, which leads to the formation of SnO 2 . Here we have varied the electron affinity of the SnSe 2 , which is very sensitive to surface oxidation, from 4.4 to 5.0 eV in steps of 0.2 eV as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%